Do Capital Flows Reflect Economic Fundamentals in Developing Countries? - Ghosh, Atish (IMF Working Papers; Working Paper ;, 1993)
This paper proposes a methodology for testing whether capital flows to developing countries are determined by economic fundamentals or by purely speculative forces. We use the intertemporal optimizing approach to current account determination as our benchmark for judging the behavior of capital flows. According to this approach, capital flows should act as a buffer to smooth consumption in the face of temporary shocks to national cash flow, defined as output less investment less government expenditures. The results are encouraging. For a large sample of developing countries, economic fundamentals are indeed found to be the most important determinant of capital flows.